2015
DOI: 10.11648/j.ijnfs.20150405.23
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical and Sensory Properties of Bread Prepared from Wheat and Unripe Plantain Composite Flours Fortified with Bambara Groundnut Protein Concentrate

Abstract: Matured, unripe plantain (Musa paradisiaca) fruits from a local cultivar, "Agbagba" were processed into flour.Protein concentrates were prepared from the flour of Bambara groundnut (Vigna subterranean L. Verde) using the alkaline extraction process. Bread was produced from the substitution levels of wheat/plantain/Bambara groundnut protein concentrate (BGPC) flour blends (100 -30%, 0 -40% and 0 -30%), respectively and the physical, chemical and sensory properties of the product evaluated. The result showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(21 reference statements)
4
0
0
Order By: Relevance
“…Moreover, the higher WAC of the composite flour could have contributed to the higher loaf weight when compared to 100% wheat bread (Okorie & Onyeneke, 2012). Similar results were reported for bread from wheat flour supplemented with non-wheat flours (David Barine, 2015). The composite bread did not show any crack formation and similar results were reported by Ukpabia & Uchechukwu (2001) on 100% Chinese yam bread.…”
Section: Physical Properties Of Bread Loavessupporting
confidence: 89%
“…Moreover, the higher WAC of the composite flour could have contributed to the higher loaf weight when compared to 100% wheat bread (Okorie & Onyeneke, 2012). Similar results were reported for bread from wheat flour supplemented with non-wheat flours (David Barine, 2015). The composite bread did not show any crack formation and similar results were reported by Ukpabia & Uchechukwu (2001) on 100% Chinese yam bread.…”
Section: Physical Properties Of Bread Loavessupporting
confidence: 89%
“…The foutou banane meals are also characterized by the low content of total dietary fiber (1.8 g/100 g dw). This value is comparable to those determined in dodo ikire (a culinary dishes made from over ripe fried plantain) reported by Kayode et al [20] where total dietary fiber content ranged from 0.8 to 2.7 g/100 g. Ash content is lower than the value of 1.3 g/100 g determined in bread produced from Wheat/Plantain/Bambara groundnut flour with 25 % plantain flour, unripe plantain cv agbagba [21]. Moreover, Aboua [22] reported higher amount of ash (2.4 g/100 g) in foutou with plantain and cassava.…”
Section: Discussionsupporting
confidence: 84%
“…Figure 1(c) illustrates that low acceptability was oriented towards high levels of both paragis powder and mashed bananas. This result was in agreement with Chima and Gernah (2007), Dachana et al (2010), Barine (2015), Emelike et al (2015), Mouminah (2015), Msaddak et al (2015), andEl-Gammal et al (2016) who reported that there was a significant decrease in the liking scores on the texture of baked products added with various types of non-conventional baking ingredients. Hafez (2012) and Aduana (2019) reported otherwise.…”
Section: Effect On Texturesupporting
confidence: 90%
“…This was clearly illustrated in Figure 1(f), which shows that high general acceptability is oriented towards low levels of powdered paragis leaves. A similar trend was observed by Dachana et al (2010), Emelike et al (2015), Mouminah (2015) and Abdel-Samie and Abdulla (2016) in cookies added with moringa powder; El-Gammal et al ( 2016) and Sengev et al (2013) in bread with powdered moringa leaves; and in cookies with plantain flour and Bambara groundnut protein concentrate (Barine, 2015). Contrarily, Hafez (2012), Ebere et al (2015), Msaddak et al (2015), and Aduana (2019) reported that added majoram in cake, cashew-apple residue in cookies, cladodes powder in cookies, and giant swamp taro powder in cookies do not significantly affect the overall acceptability of these products.…”
Section: Effect Of General Acceptabilitysupporting
confidence: 71%